(untitled) (Research, Society and Development, 2019)
The university extension has been consolidated over the last years as an essential activity of academic practice, expressing the importance of the indissociability of teaching, research and extension. In João Monlevade, in the district Baú, are located the Faculty of Engineering of the Estate University of Minas Gerais (UEMG) and the prison of the city. While the UEMG is an institution that offers teaching, research and extension for the development of science, the prison confront with problems of overcrowding, recidivism and lack of support from society. The objective of this paper is to present the project Constructing Future that made possible the change of experiences between UEMG’s teachers and students with the prisoners, through meetings with lectures, dynamics and activities of making models. The lectures addressed main themes of Civil Construction such as Bridges, Wooden Roofs, Metallic Structures, Foundations, Stairs and Electrical Installations. Constructing models allowed improving the knowledge acquired in the lectures for the construction of models that will be used during the classes, in the engineering courses of the UEMG. As a result of the meetings, it can be observed the importance of education as an instrument for rehabilitation and social reintegration of the prisoners was highlighted, during the development of the project. The project made it possible to break paradigms, reducing the prejudice that exists in working with the prison population, evidencing the high potential for the execution of jobs qualified by the prisoners. In addition, the project allowed greater integration, helping to promote the physical and mental health of the individual deprived of liberty.